Rhabdomyolysis Associated with Influenza A Virus Infection - Ibrahim, Abdisamad M (Cureus, 2018)
Influenza A associated with rhabdomyolysis has become more commonly recognized in recent years. It requires prompt recognition and treatment in order to prevent heme pigment-induced acute kidney injury. Here we report a 50-year-old female without a significant past medical history who presented with a one-week history of fevers, chills, fatigue, and generalized body aches. She was on no prior medication. Laboratory studies were significant for leukocytosis and elevated creatinine kinase up to a peak of 28,216 IU/L. Rapid influenza antigen testing was positive for influenza A virus. The patient was diagnosed with influenza A-induced rhabdomyolysis. According to our literature review, we are the first to report a case of influenza A-induced rhabdomyolysis in the 2017-2018 flu season. This case highlights the importance of considering rhabdomyolysis as a manifestation of an influenza infection.